THE WORLD IN DETAIL. NOTES ON THE MARGINS OF THE EXHIBITION CATALOGUE "LEOPOLD BUCZKOWSKI. PRZEBŁYSKI HISTORII, PRZELOTNE OBRAZKI" ("LEOPOLD BUCZKOWSKI. GLIMPSES OF HISTORY, FLEETING IMAGES") BUCZKOWSKI – WAŃKOWICZ – SCHULZ - Wasąg, Magdalena (Prace Polonistyczne, 2024)
The article presents reflections inspired by the catalogue of the exhibition Leopold Buczkowski. Glimpses of History, Fleeting Images presented at the Museum of Art in Łódź. The volume plays a significant role in presenting Buczkowski as a versatile artist, from various perspectives. It offers an important polyphony of voices from which Buczkowski emerges as a hitherto unknown writer, photographer, painter, sketcher, illustrator, and sculptor. The catalogue also helps expand the list of Buczkowski’s artistic references. The article thus examines the significance of the Borderland idiom in his works, and in this context, studies selected photographs of the Borderlands by Melchior Wańkowicz, housed in the Adam Mickiewicz Museum of Literature in Warsaw. It argues that both Wańkowicz and Buczkowski created their autobiographical story of the Borderlands as a land of their childhood thanks to photographs imbued with local flavour. Yet, Buczkowski also makes a crucial reference to works by Bruno Schulz. What they have in common are representations of hybrid (human-animal) figures and the recurrent motif of horses. Consequently, the author argues that studies of animal representations are an essential element of Galicianness in the art of Schulz and Buczkowski.